A Comparative Critical Discourse Analysis of Language Use in CNN and Al Jazeera English Media Coverage of Gaza War - Duaa Wisam Al-Muhtaseb; Rama Badwan Mohammad Qnaiby; Danya Nasser Rije; Bayan Ramzi Alhanini (Journal of Arts, Literature, Humanities and Social Sciences, 2025)
This study explores linguistic bias and media framing in the coverage of the October 7, 2023 events by CNN and Al Jazeera English. Recognizing the central role of language in shaping perceptions and influencing public opinion, especially during politically charged events, the research aims to identify linguistic differences in the two networks’ narratives, focusing on word choice, connotations, and framing strategies. Using a qualitative content analysis approach, twelve English-language news reports (six from each network) published between October 7, 2023, and January 19, 2024, were analyzed. The study examines contextual analysis (who, what, when, where, and why), language analysis ( connotation, rhetorical strategies, and voice), and global superstructure analysis (framing and source attribution). The findings reveal distinct differences in rhetorical style, source selection, and sentence structure, along with recurring narrative patterns throughout the conflict. The study concludes that news language is not neutral but strategically constructed to shape political perception, highlighting the importance of critical media literacy and deep engagement with media discourse.